Cisco networking essentials - McMillan, Troy (Serious skills., 2012)
As the world leader of networking products and services, Cisco products are constantly growing in demand. Yet, few books are aimed at those who are beginning a career in IT--until now. Cisco Networking Essentials provides a solid foundation on the Cisco networking products and services with thorough coverage of fundamental networking concepts. Author Troy McMillan applies his years of classroom instruction to effectively present high-level topics in easy-to-understand terms for beginners. With this indispensable full-color resource, you'll quickly learn the concepts, processes, and skills that are essential to administer Cisco routers and switches.